300 años: Masonerías y Masones (1717-2017). Migraciones, Tomo I, editado por Ricardo Martínez Esquivel, Yván Pozuelo Andrés y Rogelio Aragón - Ruiz Sánchez, José Leonardo (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2017)
reseña